The process for change in library education [soundrecording] - Hatfield, Frances (Los Angeles, Calif. CREDR Corp., 1973)
A session on the new directions for school library manpower project. Includes methods of recruiting, selecting, training, counseling, job placement, and involvement of the community in program development.
Tape 1. Presentations -- Tape 2. Question and answer session.
American Library Association, 91st annual conference. Media: man, material, machine.
Moderator, Robert N. Case.
Keywords: School libraries -- Congresses; Librarians -- Job descriptions -- Congresses; Librarians -- Recruiting -- Congresses; Library education -- Congresses; Library science; Education; School management